Evaluating the efficacy of mesenchymal stem cells for diabetic neuropathy: A systematic review and meta-analysis of preclinical studies - Li, Yu; Yue, Guangren; Yu, Shuying; Cheng, Xinhao; Cao, Yilin; Wang, Ximei (Frontiers in Bioengineering and Biotechnology, 2024)
Diabetic neuropathy affects nearly half of all diabetics and poses a significant threat to public health. Recent preclinical studies suggest that mesenchymal stem cells (MSCs) may represent a promising solution for the treatment of diabetic neuropathy. However, an objective assessment of the preclinical effectiveness of MSCs is still pending. We conducted a comprehensive search of PubMed, Web of Science, Embase, and Cochrane library to identify preclinical studies that investigate the effects of MSCs on diabetic neuropathy up until 15 September 2023. Outcome indicators consisted of motor and sensory nerve conduction velocities, intra-epidermal nerve fiber density, sciatic nerve blood flow, capillary-to-muscle fiber ratio, neurotrophic factors, angiogenic factors and inflammatory cytokines. The literature review and meta-analysis were conducted independently by two researchers. 23 studies that met the inclusion criteria were included in this system review for qualitative and quantitative analysis. Pooled analyses indicated that MSCs exhibited an evident benefit in diabetic neuropathy in terms of motor (SMD=2.16, 95% CI: 1.71 to 2.61) and sensory nerve conduction velocities (SMD=2.93, 95% CI: 1.78 to 4.07), intra-epidermal nerve fiber density (SMD=3.17, 95% CI: 2.28 to 4.07), sciatic nerve blood flow (SMD=2.02, 95% CI: 1.37 to 2.66), and capillary-tomuscle fiber ratio (SMD=2.28, 95% CI: 1.55 to 3.01, P<0.00001). Furthermore, after MSC therapy, the expressions of neurotrophic and angiogenic factors increased significantly in most studies, while the levels of inflammatory cytokines were significantly reduced. The relevance of this review relies on the fact that summarizes an extensive body of work entailing substantial preclinical evidence that supports the efficacy of MSCs in mitigating diabetic neuropathy. While MSCs emerge as a promising potential treatment for diabetic neuropathy, further research is essential to elucidate the underlying mechanisms and the best administration strategy for MSCs.